2018
DOI: 10.1111/pedi.12673
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status, enterovirus infection, and type 1 diabetes in Italian children/adolescents

Abstract: At the time of the clinical onset of type 1 diabetes (T1D), we investigated 82 pediatric cases in parallel with 117 non-diabetic controls matched by age, geographic area, and time of collection. The occurrence of an enteroviral infection was evaluated in peripheral blood using a sensitive method capable of detecting virtually all human enterovirus (EV) types. While non-diabetic controls were consistently EV-negative, 65% of T1D cases carried EVs in blood. The vitamin D status was assessed by measuring the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 47 publications
1
24
1
1
Order By: Relevance
“…The accurate measurement of 25 hydroxyvitamin D3 (25OHD3) status was carried out by isotope dilution mass spectrometry coupled to high-performance liquid chromatography (HPLC-MS-MS), by using the MSMS VitD Kit from PerkinElmer. It is well known that HPLC-MS-MS offers a good quantification accuracy and the contribution of interfering compounds to the final results is limited ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…The accurate measurement of 25 hydroxyvitamin D3 (25OHD3) status was carried out by isotope dilution mass spectrometry coupled to high-performance liquid chromatography (HPLC-MS-MS), by using the MSMS VitD Kit from PerkinElmer. It is well known that HPLC-MS-MS offers a good quantification accuracy and the contribution of interfering compounds to the final results is limited ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies demonstrated a link between 25(OH)D levels and diabetes, and revealed a higher frequency of vitamin D deficiency in patients with type 1 diabetes mellitus (T1DM) compared with healthy individuals [94][95][96][97]. Investigating prenatal vitamin D exposure of the fetus, a lower gestational 25(OH)D level [98] or avoiding vitamin D-fortified food [99] was significantly associated with higher risk of developing T1DM.…”
Section: Diabetesmentioning
confidence: 99%
“…A meta-analysis showed a significant association between enterovirus detection in blood and T1DM at the time of clinical onset [109]. The finding has been confirmed in multiple studies both at onset and in later phases [110115]. The MIDIA study suggested that in genetically predisposed children enterovirus infection may precede islet autoimmunity [116].…”
Section: Diabetes Mellitus and Environmental Factorsmentioning
confidence: 97%
“…Additional factors possibly involved in the origin of T1DM include breastfeeding [138], exposure to cow milk [139], exposure to Mycobacterium avium-paratubercolosis in bovine milk [140], timing of introduction of cereals [141] or egg [142], toxic chemicals such as nitrates and derivatives [143], vitamin D intake during pregnancy and thereafter [115,144]. Recently, tenuous evidence has been published for a possible causative role of influenza viruses [145].…”
Section: Diabetes Mellitus and Environmental Factorsmentioning
confidence: 99%